Study of effect of pH on ligand exchange reaction between Ni2EGTA and cyanide ion - Tripathi, P N; Singh, Anoop Kumar (Recent Research in Science and Technology, 2012)
The kinetics of ligand substitution reaction of binuclear nickel (II) chelate, Ni2L,Where L is EGTA ((ethylenedioxy) diethylenedinitrilo tetraacetic acid) with cyanide ion has been investigated spectrophotometrically. The reaction conditions are pH=11.0+ 0.1,I=0.1M (NaClO4) and temp.=25+0.10c.The formation of Ni(CN)42- is first order in Ni2L and first order in cyanide in a large range of cyanide concentration. However ,at low cyanide concentration i.e.,below 10-3 M,the reaction becomes zero order in cyanide. These results indicate the presence of a slow dissociation step in which Ni2L dissociates to give NiL2-n and Ni2+(aquo) at low cyanide concentration and a cyanide assisted rapid dissociation of Ni2L to produce NiL(CN) 22-n-x and Ni2+(aquo)at higher cyanide concentration. These species react with excess cyanide finally producing Ni(CN)42-.A five step mechanism has been proposed and the rate determining step has been identified. In this present paper, we studied the effect of pH on the reaction of cyanide ion with Ni2EGTA.